1998
DOI: 10.1016/s0969-2126(98)00047-1
|View full text |Cite
|
Sign up to set email alerts
|

High-resolution structures of variant Zif268–DNA complexes: implications for understanding zinc finger–DNA recognition

Abstract: The protein-DNA contacts observed in these complexes reveal the basis for the specificity demonstrated by these Zif268 variants. Many, but not all, of the contacts can be rationalized in terms of a recognition code, but the predictive value of such a code is limited. The structures illustrate how modest changes in the docking arrangement accommodate the new sidechain-base and sidechain-phosphate interactions. Such adaptations help explain the versatility of naturally occurring zinc finger proteins and their ut… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

7
178
1

Year Published

1999
1999
2015
2015

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 197 publications
(186 citation statements)
references
References 26 publications
7
178
1
Order By: Relevance
“…Ideally, zinc finger proteins could be readily constructed to bind any DNA sequence; however, information regarding zinc finger/DNA interactions is constrained to just a few of the 64 possible 5Ј-NNN-3Ј DNA subsites. Structural analysis of several domains that may specify a 5Ј-nucleotide other than guanine has not revealed any specific interaction from position 6 of the ␣-helix (11)(12)(13)(14)(15)(16)(17)(18)22). Thus at present it is not possible to design directly zinc finger domains that specifically bind any given 3-bp DNA subsite.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…Ideally, zinc finger proteins could be readily constructed to bind any DNA sequence; however, information regarding zinc finger/DNA interactions is constrained to just a few of the 64 possible 5Ј-NNN-3Ј DNA subsites. Structural analysis of several domains that may specify a 5Ј-nucleotide other than guanine has not revealed any specific interaction from position 6 of the ␣-helix (11)(12)(13)(14)(15)(16)(17)(18)22). Thus at present it is not possible to design directly zinc finger domains that specifically bind any given 3-bp DNA subsite.…”
Section: Discussionmentioning
confidence: 99%
“…Computer modeling of a helix binding to 5Ј-ACA-3Ј (SPA-D-LTR; Fig. 3e), based on the coordinates of finger 1 (QSG-S-LTR) of a Zif268 variant bound to 5Ј-GCA-3Ј (18), suggested that Arg 6 could easily adopt a configuration that allowed it to make a cross-strand hydrogen bond to O-4 of a thymine base-paired to the 5Ј-adenine (Fig. 7, …”
Section: ј-Ann-3ј-specific Zinc Finger Domainsmentioning
confidence: 99%
See 2 more Smart Citations
“…Borges and Collins 112 described that buffers, such as tricine (pH 8.0, 20 mmol l À1 ), affect the high-performance liquid chromatography (HPLC) stability and performance of study have themselves high complexing capabilities and buffer interference is thought to be simply nonexistent. These studies involve proteins with heme groups, [134][135][136] Zn-nger motifs, [137][138][139] metalloproteins 116,133,[140][141][142] and/or other complexing agents in solution. 81,[143][144][145] In fact, the concentrations of the compounds used, and most importantly the ratio of the buffer concentration to the complexing compound concentration in the medium, are within values that support the idea that no interference of the buffer occurs.…”
Section: Hepesmentioning
confidence: 99%